2015
DOI: 10.1186/s13071-015-1283-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oral declaration on adherence to ivermectin treatment and parasitological indicators of onchocerciasis in an area of persistent transmission despite a decade of mass drug administration in Cameroon

Abstract: BackgroundOnchocerciasis control for years has been based on mass drug administration (MDA) with ivermectin (IVM). Adherence to IVM repeated treatment has recently been shown to be a confounding factor for onchocerciasis elimination precisely in rain forest areas where transmission continues and Loa loa co-exists with Onchocerca volvulus. In this study, participants’ oral declarations were used as proxy to determine the relationship between adherence to IVM treatment and parasitological indicators of onchocerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 51 publications
(83 reference statements)
4
30
1
Order By: Relevance
“…The odd of noncompliance among the diseased was nearly four times more probable than the odd of noncompliance among nondiseased. The finding was in line with studies done in Cameroon, which showed that compliance with ivermectin treatment was independently associated with onchocerciasis infection [20].…”
Section: Discussionsupporting
confidence: 91%
“…The odd of noncompliance among the diseased was nearly four times more probable than the odd of noncompliance among nondiseased. The finding was in line with studies done in Cameroon, which showed that compliance with ivermectin treatment was independently associated with onchocerciasis infection [20].…”
Section: Discussionsupporting
confidence: 91%
“…So, the likelihood to confuse them with other drugs or interventions is quite low. Previous studies have reported accurate recall of populations when compared to the data from CDTI collected in treatment registry [4143]. …”
Section: Discussionmentioning
confidence: 99%
“…So, the likelihood to confuse them with other drugs or interventions is quite low. Previous studies have reported accurate recall of populations when compared to the data from CDTI collected in treatment registry [ 43 45 ]. The presence of the disease in less than 10-year-old children is another threat as it means that the adult worms they carried, still have a lifespan of at least 5 to 10 years, constituting a source of reinfestation.…”
Section: Discussionmentioning
confidence: 99%